Chemicals from biomass : integrating bioprocesses into chemical production complexes for sustainable development - Sengupta, Debalina; Pike, Ralph W., 1935- (Boca Raton : CRC Press, 2013)
'Identifying and designing new chemical processes that use renewable feedstock as raw materials and show how these processes can be integrated into existing chemical production complexes are key to having a sustainable chemical industry. Also, identifying and designing new industrial processes that use carbon dioxide as a raw material are an important option in mitigating the effects of global warming'--
1. Introduction -- 2. Biomass as feedstock -- 3. Chemicals from biomass -- 4. Simulation for bioprocesses -- 5. Bioprocesses plant model formulation -- 6. Formulation and optimization of the superstructure -- 7. Case studies using superstructure.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: Biomass chemicals; Energy crops -- Biotechnology; Sustainable development